Answer:
x =
![(4+5y)/(y+3)](https://img.qammunity.org/2022/formulas/mathematics/high-school/ro9tu0jz3u33a75tonl3m37uensk7u7l7m.png)
Explanation:
Given
y =
( multiply both sides by x - 5
y(x - 5) = 4 - 3x ( distribute left side )
xy - 5y = 4 - 3x ( add 3x to both sides )
xy + 3x - 5y = 4 ( add 5y to both sides )
xy + 3x = 4 + 5y ← factor out x from each term on the left side
x(y + 3) = 4 + 5y ← divide both sides by y + 3
x =
![(4+5y)/(y+3)](https://img.qammunity.org/2022/formulas/mathematics/high-school/ro9tu0jz3u33a75tonl3m37uensk7u7l7m.png)